Old Age Prejudice in Mexican University Students: Comparisons by Gender - Garcia, Perla Jannet Jurado; Vásquez, Susana Ivonne Aguirre; Bencomo, Edgar Francisco Ordonez; Vega, Humberto Blanco; Enriquez, Maria del Carmen Zueck; Perez, Jesus Enrique Peinado; Ornelas, Jose Rene Blanco (European Scientific Journal, ESJ, 2020)
The goal of the present research was to compare the profiles of old age prejudice in male and female students from the area of physical activity. The study was conducted from January to October 2016. Participants were recruited from different semesters of the Physical Education and Human Motricity bachelor’s degrees offered at the Faculty of Physical Culture Sciences of the Autonomous University of Chihuahua, Mexico. The sample was obtained through convenience sampling, and included 1652 participants; 828 women and 824 men, mean age was 20.51 ± 1.83 years 20.90 ± 2.03 years respectively. The approach of the study was quantitative with a descriptive survey-like design. All participants completed the Questionnaire on Negative Stereotypes towards Old Age. Results from the Multivariate Analyses of Variance, and the follow-up Univariate Analyses of Variance, show that men report greater levels of prejudice towards old age on the sociomotivational (F = 31.657, p<.001) and character-personality (F = 15.789, p<.001) factors. No differences were found on the health factor (i.e., mental and physical). These results suggest that when designing any type of intervention in which the purpose isto improve the perception of young people towards the elderly, the variable gender should be considered. Future research should replicate these findings in larger samples.